The Challenge of Teacher Islamic Religion During an Endemi Transition: the Study of Phenomenon at Elementary School Level - Sallima, Alfi Nur Hidayatus; Romadlon, Dzulfikar Akbar (research, training and philanthropy institution Natural Aceh, 2024)
After about two years, the pandemic has hit the world, including education. During the endemic transition period, the recovery phase regarding the impacts and challenges teachers face is an important matter to pay attention to, how teachers, institutions, and the government restore current learning due to yesterday's online education. We conducted the research on the outskirts of Sidoarjo, precisely in the Tarik sub-district, directly adjacent to Mojokerto. So, the author has a goal in this study to see how PAI teachers feel about the Impacts and Challenges at the elementary level. This study used a qualitative research approach, with phenomenological methods and data collection techniques using interviews, observation, and documentation. This study used purposive sampling as a data collection technique. The subject of this research was a PAI teacher at an SD and MI in the Tarik-Sidoarjo area. The study's results and conclusions stated that learning carried out online impacted the current learning process, where student learning motivation decreased due to yesterday's online learning. In addition, digital literacy is a challenge for Islamic education teachers today. In the implication during this endemic transition period, the impacts and challenges teachers feel can be evaluated in the education sector in Indonesia so that they are better.